Dam regional safety warning using time-series InSAR techniques - Roque, D. (2015)
Accurate and frequent monitoring of dams and its surroundings is an extremely important task to ensure the safety of settlements located downstream. Time-series InSAR techniques are a cost-effective way for measuring millimeter-level displacements on the Earth surface, at a regional scale, and can be used as an early warning system for the safety of structures and their surroundings. This study presents the application of one of these techniques to the earth dams Álamos I and Álamos II, in Portugal. The results obtained for Álamos I were compared to geodetic measurements and it was verified that the maximum difference of the average displacement rate between the two techniques is 3.2 mm/yr. Preliminary processing was performed for the concrete dam Alqueva.